Proteomic Strategies for the Analysis of Carbonyl Groups on Proteins - Irazusta, Verónica Patricia (2010)
Oxidative stress is caused by an imbalance between formation and destruction of reactive oxygen species. Analysis of the reaction products of reactive oxygen species in biomolecules is an indirect way of determining the existence of oxidative stress. In this context, the formation of carbonyl groups in proteins has been one of the most studied oxidative stress markers because of its stability and easy detection. Various proteomic tools offer great potential for the discovery of new proteins susceptible to oxidative stress, determination of quantitative changes in the profile of these modifications under different biological conditions, and characterization of the type of modification a particular protein has suffered. This paper reviews the different approaches used for the detection of protein carbonyls and the proteomic tools that can be used to identify them.